An Interprofessional Yearlong Geriatrics Fellowship Program for Advanced Practice Nursing and Social Work Students. Issue 5 (3rd September 2022) - Glassburn, Susan; Frank, Kathryn; Fulton, Jan; Westmoreland, Glenda; Garrison, Emilie; Roth, Sarah; Litzelman, Debra K.
Abstract : Background: The care of older adults with complex medical conditions requires effective team-based care. Problem: Nursing and social work students need a curriculum that provides them with immersive experiences in geriatrics to prepare them for competent practice. Approach: This Geriatric Workforce Enhancement Program supported 5 advanced practice nursing (APN) and 5 master of social work (MSW) student fellows in a 2-semester program, with 3 cohorts completing the fellowship over 3 years (N = 30). Outcomes: By the completion of the fellowship, students had (1) demonstrated increased knowledge of age-related changes and health problems experienced by older adults, (2) developed clinical competencies in providing patient-centered health care for older adults, and (3) assessed the fellowship as helpful in preparing for interprofessional team care. Conclusions: An interprofessional gerontology fellowship for APN and MSW students can develop knowledge and skills in team-based care for older adults. Recommendations for creating a fellowship curriculum are provided.